2021
DOI: 10.3390/toxins13090658
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin Protein Is Involved in the Action of Bacillus thuringiensis Cry1Ac Toxin in Ostrinia furnacalis

Abstract: Transgenic crops expressing Bacillus thuringiensis (Bt) insecticidal proteins have been extensively planted for insect pest control, but the evolution of Bt resistance in target pests threatens the sustainability of this approach. Mutations of cadherin in the midgut brush border membrane was associated with Cry1Ac resistance in several lepidoptera species, including the Asian corn borer, Ostrinia furnacalis, a major pest of maize in Asian–Western Pacific countries. However, the causality of O. furnacalis cadhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…A later study characterized the alteration of aminopeptidase N and ABC type G transcripts in both the ACB-AbR colony (studied here) and the ACB-AcR colony [21]. Recently, the involvement of the O. furnacalis cadherin in the toxicity of Cry1Aa and Cry1Ac was proven through CRISPR knock-outs [22], as well as the ABCC2 in the toxicity of Cry1F and Cry1Ab/c [23]. The binding sites here proposed could be located in some of these receptors or even in different epitopes of the same one, as has been shown for Cry1A proteins and the ABCC2 transporter in Spodoptera exigua [24,25].…”
Section: Discussionmentioning
confidence: 92%
“…A later study characterized the alteration of aminopeptidase N and ABC type G transcripts in both the ACB-AbR colony (studied here) and the ACB-AcR colony [21]. Recently, the involvement of the O. furnacalis cadherin in the toxicity of Cry1Aa and Cry1Ac was proven through CRISPR knock-outs [22], as well as the ABCC2 in the toxicity of Cry1F and Cry1Ab/c [23]. The binding sites here proposed could be located in some of these receptors or even in different epitopes of the same one, as has been shown for Cry1A proteins and the ABCC2 transporter in Spodoptera exigua [24,25].…”
Section: Discussionmentioning
confidence: 92%
“…Several studies in the literature have reported that Cry toxin receptors are located in BBM, including cadherin-like (Aimanova et al 2006 ; Zhang et al 2020 ; Jin et al 2021 ), aminopeptidase N (APN) (Wei et al 2016 ; Shao et al 2018 ), and alkaline phosphatase (ALP) (Likitvivatanavong et al 2011 ; Stalinski et al 2016 ). The activated toxin samples from the different formulated products analyzed in this work showed similar binding to BBMV from two lepidopteran insects.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we were persistent to generate the Aae-Cad KO in A . aegypti , since previous works have successfully generated the Cad KO mutations in lepidopteran species using CRISPR-Cas9 technology and the role of this protein as a functional receptor for Cry toxins has been demonstrated [ 24 , 25 , 27 , 28 ]. Our CRISPR-Cas9 KO mutations in the aae-cad gene resulted in the generation of premature stop codons in the mRNA.…”
Section: Discussionmentioning
confidence: 99%